The communication language and the fair trial in Cameroon - Cyrille, Monkam (Comparative Legilinguistics, 2024)
This paper deals with the incidence of communication channels treatment during court proceedings in a multilingual context like Cameroon. On the one hand, I will defend on the one hand the idea according to which the unbalanced treatment enshrined in the constitution, which confers preferential treatment to the so-called official, but imported languages and a marginal role to other local languages termed as national as well as other means of expression, affects the communication before courtrooms. The use of the former is reserved for an elitist minority group while that of the latter for a majority illiterate group. On the other hand, there has been an effort on the part of the state to curb this discrimination through the linguistic assistance. But still, there are challenges that confirm the legitimate fears of litigants, better lay-litigants of violation of their rights of access to justice and fair trial at large. The paper then suggests to the State to enhance the promotion of national languages, to emphasize on the training of judicial personnel and public awareness.